ENVIRONMENTAL SERVICE WORKERS PERCEPTION OF WORKING AT COVID-19 REFERRAL HOSPITAL IN KLATEN - Ontivia Setiani Wahana; - Kusbaryanto; Arlina Dewi (Jambura Journal of Health Sciences and Research, 2021)
Background: Working in the COVID-19 pandemic era isn't easy, especially for personnel who work in COVID-19 referral hospitals. Non-medical workers such as environmental service workers (ESW) also experience changes in regulations at work. ESW in isolation ward are included in the high exposure risk category because of their high potential for close contact with COVID-19 patients. This study aims to analyze the ESW's perception of working at the COVID-19 referral hospital in Klaten.Methods: This is a descriptive qualitative study with a phenomenological approach. Four respondents were obtained for interviews.Results: The results show that ESW's understanding of COVID-19 hasn't been maximized and evenly distributed, there are obstacles and changes of habits, in the work system and service standards that create inconvenience while working, psychological impacts; both negative and positive feelings appear while working during this pandemic. However, ESW still work professionally, have a good work commitment to reduce the risk of nosocomial infections including preventing the spread of the virus.Conclusion: ESW's perceptions related to COVID-19 hasn't been evenly distributed. Mandatory use of personal protective equipment in the pandemic era, causes discomfort and obstacles to work. This pandemic triggered the emergence of negative emotions that are dominant over positive emotions. However, ESW can still work professionally.